The Effect of Planting Time and Scheme on the Yield of False Stem of Leek - Vokhidov Sarvarbek Tolanboy o’g’li; Nosirov Iqboljon Kabiljon o’g’li (European Journal of Life Safety and Stability (2660-9630), 2024)
In the article, the control of leek varieties "Vesta" and "Elefant MS" suitable for the soil and climate conditions of the Fergana Valley was 53.6 and 51.3 t/ha (respectively) during the February 20 planting period, compared to 10- in February 4.0-5.4 tons of high false stem yield and the highest false stem yield compared to the 70×15 cm (control) scheme (19.8 and 20.0 t/ha) 50+20/2×5 cm (72 ,1 and 70.4 t/ha) and 50+20/2×15 cm (51.5 and 52.6 t/ha) planting schemes showed 29.8-34.5% less false stem yield 70 It is highlighted that in the ×20 cm planting scheme (5.9 and 6.9 t/ha, respectively).